A Documentary Review of Multidimensional Thinking, Thinking Skills and Assessment in Philosophy for Children (P4C) - Gallo-Bohórquez, Linda Brigitte; García-Gutiérrez, Zaily del Pilar; Cortés-Estupiñan, Andrea (Revista Electrónica Educare, 2023)
Introduction. The education of children demands new training proposals, which are more pertinent for developing their potential, for which P4C is a new philosophical and educational alternative. Aim. To carry out a systematic study based on the documentary review methodology that describes multidimensional thinking, thinking skills, and evaluative experiences in P4C. Method. Based on the documentary review methodology, after the study of 64 documents, the categories of analysis are established as multidimensional thinking, thinking skills, and evaluation. Results. As the main findings, the strengthening of multidimensional thinking as a contribution of P4C to early childhood education, its benefits, together with the role of the facilitator for the development of thinking skills; and the evaluative methodologies in favor of the development of multidimensional thinking in children stand out. Conclusion. The research reveals that P4C manages a reciprocal and bidirectional relationship between the development of multidimensional thinking, thinking skills, and evaluation, from which it mobilizes pertinent educational actions for early childhood education.